Morphological revision of the hyperdiverse Brueelia-complex (Insecta: Phthiraptera: Ischnocera: Philopteridae) with new taxa, checklists and generic key - Gustafsson, Daniel R.; Bush, Sarah E. (Zootaxa, 2017)
The genus Brueelia Kéler, 1936a forms the core of the so-called “Brueelia-complex”, one of the largest and most heterogeneous groups of lice (Phthiraptera). Here we introduce the taxonomic history and present a revision of this group. The limits of the Brueelia-complex are discussed. We resurrect the genera Acronirmus Eichler, 1953, Corvonirmus Eichler, 1944, Guimaraesiella Eichler, 1949, Maculinirmus Złotorzycka, 1964a, Meropsiella Conci, 1941a, Olivinirmus Złotorzycka, 1964a, Osculonirmus Mey, 1982a, Rostrinirmus Złotorzycka, 1964a, Traihoriella Ansari, 1947, and Turdinirmus Eichler, 1951. We describe the following new genera: Anarchonirmus n. gen., Aporisticeras n. gen., Aratricerca n. gen., Buphagoecus n. gen., Ceratocista n. gen., Sychraella n. gen., Couala n. gen., Harpactrox n. gen., Hecatrishula n. gen., Indoceoplanetes n. gen., Manucodicola n. gen., Mirandofures n. gen., Nemuus n. gen., Priceiella n. gen., Psammonirmus n. gen., Resartor n. gen., Saepocephalum n. gen., Schizosairhynchus n. gen., Teinomordeus n. gen., Titanomessor n. gen., and Turdinirmoides n. gen.; and the following new subgenera: Camurnirmus n. subgen., Thescelovora n. subgen., Torosinirmus n. subgen., and Capnodella n. subgen.        The following 37 new species are described: Anarchonirmus albovittatus n. sp. ex Pomatostomus temporalis strepitans (Mayr & Rand, 1935); Brueelia aguilarae n. sp. ex Euplectes franciscanus pusillus (Hartert, 1901); Brueelia phasmasoma n. sp. ex Coereba flaveola luteola (Cabanis, 1850); Brueelia pseudognatha n. sp. ex Pycnonotus nigricans superior Clancey, 1959; Sychraella sinsutura n. sp. ex Pomatostomus isidorei isidorei Lesson, 1827; Couala dodekopter n. sp. ex Coua cristata pyropyga Grandidier, 1867; Guimaraesiella pandolura n. sp. ex Pericrocotus flammeus semiruber Whistler & Kinnear, 1933; Harpactrox geminodus n. sp. ex Harpactes erythorcephalus erythrocephalus (Gould, 1834); Harpactrox loeiensis n. sp. ex Harpactes erythrorhynchus annamensis (Robinson & Kloss, 1919); Harpactrox pontifrons n. sp. ex Harpactes ardens ardens (Temminck, 1824); Indoceoplanetes (Capnodella) loboccupatrix n. sp. ex Lobotos oriolinus Bates, 1909; Indoceoplanetes (Capnodella) laurocorythes n. sp. ex Edolisoma holopolium holopolium (Sharpe, 1888); Maculinirmus ljosalfar n. sp. ex Oriolus chinensis diffusus Sharpe, 1877; Manucodicola acantharx n. sp. ex Manucodia ater ater (Lesson, 1830); Manucodicola semiramisae n. sp. ex Phonygammus keraudrenii purpureoviolaceus (Meyer, 1885); Meropoecus balisong n. sp. ex Merops americanus Muller, 1776; Meropoecus bartlowi n. sp. ex Merops ornatus Latham, 1802; Mirandofures altoguineae n. sp. ex Oreostruthus fuliginosus De Vis, 1898; Mirandofures kamena n. sp. ex Erythrura trichroa sigillifer (De Vis, 1897); Nemuus hoedhri n. sp. ex Artamus fuscus Vieillot, 1817; Nemuus imperator n. sp. ex Artamus maximus Meyer, 1874; Priceiella (Camurnirmus) hwameicola n. sp. ex Garrulax taewanus Swinhoe, 1859; Priceiella (Camurnirmus) paulbrowni n. sp. ex Garrulax leucolophus diardi (Lesson, 1831); Priceiella (Thescelovora) alliocephala n. sp. ex Platylophus galericulatus ardesiacus (Bonaparte, 1850); Priceiella (Torosinirmus) koka n. sp. ex Turdoides tenebrosa (Hartlaub, 1883); Psammonirmus lunatipectus n. sp. ex Serilophus lunatus lunatus (Gould, 1834); Aratricerca cirithra n. sp. ex Ptiloprora guisei guisei (De Vis, 1894); Saepocephalum stephenfryi n. sp. ex Corcorax melanoramphos (Vieillot, 1817); Schizosairhynchus erysichthoni n. sp. ex Aplonis metallica metallica (Temminck, 1824) and Aplonis metallica nitida (Grey, 1858); Schizosairhynchus minovenator n. sp. ex Mino dumontii Lesson, 1827; Sturnidoecus australafricanus n. sp. ex Corvinella melanoleuca expressa Clancey, 1961; Sturnidoecus mon n. sp. ex Euplectes hordeaceus (Linnaeus, 1758); Sturnidoecus porphyrogenitus n. sp. ex Cinnyricinclus leucogaster verreauxi (Bocage, 1870); Sturnidoecus somnodraco n. sp. ex Quelea quelea quelea (Linnaeus, 1758) and Qualea quelea lathami (Smith, 1836); Teinomordeus entelosetus n. sp. ex Eurocephalus rueppelli Bonaparte, 1853; Titanomessor sexloba n. sp. ex Laniarius erythrogaster (Cretzschmar, 1829); and Turdinirmus australissimus n. sp. ex Zoothera lunulata lunulata (Latham, 1802). The name Olivinirmus paraffinis nom. nov. is proposed as a replacement for the preoccupied Brueelia affinis Carriker, 1963. We place 23 names in synonymy, and we consider 6 species as incertae sedis, 2 names as nomina nuda, and transfer 14 species names to genera not belonging to the Brueelia-complex.        We redescribe and illustrate most of the type species of the genera or subgenera included in this revision. Keys to genera, subgenera, and species groups are given, together with updated louse-host and host-louse checklists for 426 species of lice currently placed in the Brueelia-complex, including 183 new host-louse records.